2013
DOI: 10.5489/cuaj.909
|View full text |Cite
|
Sign up to set email alerts
|

Residual renal function after partial or radical nephrectomy for renal cell carcinoma

Abstract: Renal cell carcinoma (RCC) is often detected incidentally and early. Currently, open partial nephrectomy and laparoscopic total nephrectomy form competing technologies. The former is invasive, but nephron-sparing; the other is considered less invasive but with more loss of renal mass. Traditionally, emphasis has been placed on oncologic outcomes. However, a patient with an excellent oncologic outcome may suffer from morbidity and mortality related to renal failure. Animal models with hypertension and diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 57 publications
2
33
0
3
Order By: Relevance
“…Activation of the TGF system will begin afferent arteriolar vasoconstriction [59]. In accord with Chapman et al [3], the present study showed increase in GFR in the remaining renal tissue following the nephrectomy as consequence of TGF system activation that allowing higher early distal flow rates.…”
Section: Journal Of Complementary Medicine and Alternative Healthcaresupporting
confidence: 89%
See 3 more Smart Citations
“…Activation of the TGF system will begin afferent arteriolar vasoconstriction [59]. In accord with Chapman et al [3], the present study showed increase in GFR in the remaining renal tissue following the nephrectomy as consequence of TGF system activation that allowing higher early distal flow rates.…”
Section: Journal Of Complementary Medicine and Alternative Healthcaresupporting
confidence: 89%
“…The renal clearance of endogenous creatinine is widely used to assess GFR and renal function in animal investigations [52]. In conjunction with the reports of Bohlouli et al [53] and Chapman et al [3], the present study revealed significant increase in creatinine clearance following unilateral nephrectomy in rats. Mueller & Luyckx [54] reported increase in GFR by 60%-70% following uni-nephrectomy in the remaining kidney.…”
Section: Journal Of Complementary Medicine and Alternative Healthcaresupporting
confidence: 84%
See 2 more Smart Citations
“…[12] The anemia of CKD increases morbidity and mortality from cardiovascular complications which may lead to further deterioration of renal function. [13] Red cell production due to the Erythropoietin deficiency is too low in CRF and causes development of anemia in this situation. Anemia is also seen in patients with acute renal failure but the exact relationship between them remained unclear.…”
Section: Introductionmentioning
confidence: 99%